Протестантські релігійні громади Південної України та Комуністична партія в роки перебудови (за матеріалами радянських партійних архівів) - Михайлов, Володимир Вікторович; Михайлов, Владимир Викторович; Mykhailov, Volodymyr (My University, 2019)
UK: У статті на основі матеріалів державних обласних архівів проаналізовано чисельність, динаміку розвитку та специфіку діяльності протестантських конфесій на території Південної України у період перебудови другої половини 1980-х - 1991 рр. Автором встановлено, що найактивнішими проте-стантськими деномінаціями у регіоні були євангельські християни-баптисти, п’ятидесятники, свідки Ієгови та адвентисти сьомого дня. До основних форм діяльності релігійних об’єднань слід віднести проведення богослужінь і обрядів та поширення релігійної літератури серед населення. Демократизація радянського суспільства, яка відбувалася внаслідок реформ М. Горбачова у др. пол. 1980-х рр., призвела до зміни державно-церковних відносин. На тлі загальних процесів лібералізації в СРСР, комуністична влада обмежує своє втручання в релігійні справи. За нових умов релігійна політика держави базувалася на встановленні контролю над діяльністю релігійних громад та вдосконаленні форм і засобів атеїстичного виховання населення. EN: The dynamics of the development, the quantitative composition and the specificity of the organizational forms of the Protestant confessions in the territory of the Southern Ukraine during the period of the perestroika of the second half of 1980 – 1991 were analyzed in the article on the basis of the materials of the state regional archives. The peculiarities of the development of the Protestantism in the South of Ukraine are considered as the integral complex of the part of the all-Ukrainian religious opposition movement. The most active Protestant denominations in the region were the evangelical Christians-Baptist, Pentecostals, Jehovah’s Witnesses and the Seventh-day Adventists were determined by the author. In the Southern Ukraine, the Protestant communities were distributed in all spheres which had the formed network, and they were the second in number after the Orthodox. To the main forms of the activities of the religious associations should be carried away the realization of the public worship and the ceremonies and the dissemination of the religious literature among the population. The Communities of the late Protestantism were under the constant administrative pressure and they were the object of the party-ideological criticism and the atheistic propaganda. The democratization of Soviet society happened because of the result of M. Gorbachev’s reforms in the 2nd half of 1980s which led to the changes of the state-church relations. On the background of the general processes of the liberalization in the USSR, the communist government limits its interference in the religious affairs. Under the new conditions, the religious policy of the state was based on the installation of the control over the activity of the religious communities and the improve of the forms and the means of the atheistic education of the population. The ideological structures of the party apparatus were directed at the carrying out the propagandistic anti-religious measure, with the purpose of the decrease of the religious rituals and the reduction of the number of the believers. The facts are presented in the article show that the Protestantism was spread and strengthened its position in the USSR as the whole and in the particular in the South of Ukraine.
The protestant religious communities of the Southern Ukraine and the Communist Party during the years of the perestroika (on the materials of the Soviet party archives)
Keywords: період перебудови; державно-церковні відносини; протестантські громади; Комуністична партія України; Південна Україна; period of perestroika; state-church relations; Protestant communities; Communist Party of Ukraine; the Southern Ukraine